(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Steganography, derived from the Greek term meaning "covered writing," is the art and science of concealing hidden messages within seemingly innocuous communications, ensuring that only the sender and the intended recipient are aware of the message’s existence. This method provides security through obscurity, differentiating itself from other data-hiding techniques by embedding a secret message within an existing channel of communication. Unlike covert channel techniques that establish a new connection between previously unconnected entities, steganography aims to conceal messages within "harmless" communications, making it undetectable to any potential eavesdroppers or adversaries. The crux of steganography lies in the secret key—a short, easily exchangeable random number sequence. Without this key, an adversary would not even suspect the presence of hidden communication within the observed channel. This technique is particularly relevant in scenarios where encrypted communication is not permitted, such as in certain corporate environments or under specific government regulations. Steganography also intersects with the issue of "hidden channels" in secure operating system design, which involves communication paths that are difficult for access control mechanisms to restrict. In these contexts, steganography provides a viable alternative, allowing covert communication without raising suspicion or violating policies against encrypted messages.